Assessing Rates of Consumption in Newly Restored Seagrass Beds Across a Depth Gradient - Smith, Dawsyn Alyssa (East Carolina University, 2022)
Seagrass is a critical habitat for many marine species, however it is being lost at an alarming rate globally. To combat the rapid loss of seagrass habitats, efforts to restore seagrass are increasing. While restoration practices have increased in efficacy as understanding of best practices has improved, it is still unclear how different restoration approaches may impact fauna using seagrass beds as habitat. The two main research questions for this project are, “How do faunal consumption rates differ across depth, subtidal and intertidal, of restored seagrass beds?” and “How do consumption rates differ between faunal habitat types?” To answer these questions, I monitored consumption rates within (1) intertidal and subtidal restored seagrass beds, (2) intertidal and subtidal bare sand, (3) intertidal natural seagrass beds; and (4) adjacent to intertidal oyster reefs. Consumption assays consisted of “squid pops” (dried squid attached to garden stakes) being deployed in all 31 plots one hour prior to low-tide and then checked after one, two, and 24 hours. After one hour, higher consumption rates were observed in deep versus shallow plots, regardless of plot type. After the second hour and after 24 hours, there was no difference in consumption by depth or plot type, with 100% consumption observed within 24 hours across all plots. When comparing consumption across intertidal habitat types after 2 hours, the highest consumption rates were observed adjacent to oyster reefs, followed by within natural seagrass, then sand flat, and lastly restored seagrass, with 100% consumption observed across all plots within 24 hours. Greater understanding of how depth and restoration approaches can impact faunal consumption rates can ensure the future sustainability of restored seagrass beds as a habitat for fauna.
Keywords: seagrass restoration; consumption rate